Cardiac Myosin Epitopes Recognized by Autoantibody in Acute and Convalescent Rheumatic Fever. Issue 9 (September 2016) - Garcia, Alan F.; Yamaga, Karen M.; Shafer, Leigh Anne; Bollt, Oana; Tam, Elizabeth K.; Cunningham, Madeleine W.; Kurahara, David K.
Abstract : Background: Acute rheumatic fever (ARF) is an autoimmune disorder associated with Streptococcus pyogenes infection. A prevailing hypothesis to account for this disease is that epitopes of self-antigens, such as cardiac myosin react to antibodies against S. pyogenes . The goal of our study was to confirm disease epitopes of cardiac myosin, identify immunodominant epitopes and to monitor the epitope response pattern in acute and convalescent rheumatic fever. Methods: Enzyme-linked immunosorbant assays were used to determine epitopes immunodominant in acute disease and to track the immune response longitudinally to document any changes in the epitope pattern in convalescent sera. Multiplex fluorescence immunoassay was used to correlate anti-streptolysin O (ASO) and anti-human cardiac myosin antibodies. Results: Disease-specific epitopes in rheumatic fever were identified as S2-1, 4 and 8. Epitopes S2-1, 4, 8 and 9 were found to be immunodominant in acute sera and S2-1, 8, 9, 29 and 30 in the convalescent sera. Frequency analysis showed that 50% of the ARF subjects responded to S2-8. S2-8 responders tended to maintain their epitope pattern throughout the convalescent period, whereas the S2-8 nonresponders tended to spread their responses to other epitopes later in the immune response. There was a significant correlation between anti-cardiac myosin and ASO titers. In addition, S2-8 responders showed elevated ASO titers compared with S2-8 non responders. Conclusion: Our studies confirm the existence of S2-1, 4 and 8 as disease-specific epitopes. We provide evidence that cardiac myosin S2-8 responders remain epitope stable in convalescence, whereas S2-8 nonresponders shift to neoepitopes. Multiplex data indicated a correlation between elevated ASO and anti-human cardiac myosin antibody titers. Mapping of cardiac myosin epitopes recognized in rheumatic fever sera may identify immunophenotypes of rheumatic fever. Abstract : Supplemental Digital Content is available in the text.